Quality of Service in Providing Financial Management Services for Public Service Agency at Universitas Negeri Manado - Mongdong, Deiby; Sendouw, Recky H. E.; Kantohe, Meidy (Technium Social Sciences Journal, 2023)
The quality of the financial services of the Public Service Agency (BLU) at Universitas Negeri Manado should be able to provide good results wherever possible. The State Civil Apparatus within the Universitas Negeri Manado Personnel, Finance, and General Bureau has a very strategic role as the spearhead of public planning. The aim of this research is to determine, describe, and analyze the Quality of Financial Management Services for the Universitas Negeri Manado Public Service Agency (BLU) in 2022. The method used is a qualitative research method. Based on research in the field, it can be concluded that the 5 indicators of service quality, namely tangible, reliability, responsiveness, assurance, and empathy, which were researched at the Universitas Negeri Manado Personnel, Finance and General Bureau (BKKU), have gone well. This can be seen from the answers of the informants and documentary evidence as well as the circumstances studied. However, there are several things that need to be improved so that service users can be more satisfied in the future.